`Friends as enemies`: A sociological analysis of the relationship among touring professional golfers - Fry, J.; Bloyce, D. (International Review for the Sociology of Sport, 2017)
This paper examines the relationship among male touring professional golfers from a figurational sociological standpoint. The paper is based on 20 interviews from players with experience playing at various levels on the European Professional Golfers Association professional tours and a level `above` that. The results indicate a workplace culture where many begin to adopt the attitudes and behaviors that encourage the development of networks of temporary `we-group` alliances. The `touring` aspects of professional golf means many players strive to forge these alliances to help reduce feelings of loneliness, isolation, and homesickness while away for long periods of time. Such stresses are intensified given the globalization of sport generally and the associated increases in labor market migration that have become commonplace. The urge to develop friendship networks constrains players to behave in a manner expected of them rather than in a way that reflects their actual emotions, such as maintaining a positive attitude during difficult times like spells of poor performances and time away from their families. The relationships among players on tour are, however, nonpermanent and/or partially changeable. Players are `friends`, characterized by togetherness and camaraderie, while, at the same, showing evidence of tensions and conflict as they are ultimately in direct competition with each other for a share of the overall prize money.